Correlation of Troponin-I with Angiographic Profile in Patients of Unstable Angina - Akteruzzaman, M; Rahman, A; Rahman, A; Miah, MNA; Haque, J; Rahman, A (Bangladesh Journal of Medicine, 2013)
Bangladesh Journal of Medicine, Vol 24 No 1, 2013, Page 5-9 DOI: http://dx.doi.org/10.3329/bjmed.v24i1.15028